Abandoned construction: Factors and ways to circumvent abandoned housing projects in Peninsular Malaysia - Hassan Baderi, Siti Norehan; Muhammad Najid, Nor Rashidah; Rusli, Roseleda; Mohd Nawi, Mohd Nasrun; Osman, Wan Nadzri (2013)
Abandoned housing projects are one the major problems in the housing industry in Peninsular Malaysia.A housing project is considered abandoned when construction activities on-site housing construction has ceased for 6 (six) months or more in a row, after the completion of the sale and purchase agreement has been signed by the developer and the buyer or the developer has put under the control of the Official Receiver and Controller of Housing.This paper reviewed information on the current issues of causes of occurrence of abandoned projects.The reasons leading to this problem are many.This catastrophe has caused multifarious problems to the stakeholders, particularly the purchasers who become the aggrieved parties.Until to date there is no effective and once-and-for-all means to face the problems of abandoned housing projects. This project aims to analyze the factors of existence abandoned housing project in Peninsular Malaysia and find the best way to revive this abandoned housing project.